Factor VIII inhibitor bypass activity (FEIBA) for the reduction of transfusion in cardiac surgery: a randomized, double-blind, placebo-controlled, pilot trial - Valerie A. Sera; Ann E. Stevens; Howard K. Song; Victor M. Rodriguez; Frederick A. Tibayan; Miriam M. Treggiari (Pilot and Feasibility Studies, 2021)
Abstract Background Uncontrolled bleeding after cardiac surgery can be life-threatening. Factor eight inhibitor bypassing activity (FEIBA) is a prothrombin complex concentrate empirically used as rescue therapy for correction of refractory bleeding diathesis post-cardiopulmonary bypass (CPB). FEIBA used as rescue therapy for bleeding diathesis after CPB has been associated with a low incidence of complications and a reduction in transfusion requirement and re-exploration. The feasibility and efficacy of early administration of FEIBA after the termination of CPB have not been studied in a prospective randomized trial. Methods We designed a small randomized, double-blinded, placebo-controlled pilot trial to determine the feasibility of a larger trial testing the hypothesis that FEIBA decreases transfusion requirements after CPB. The study was designed to evaluate the feasibility of a larger pivotal trial to determine the effectiveness of FEIBA in reducing the total volume of blood products transfused perioperatively, and its safety profile. Study participants were adult patients undergoing elective major aortic cardiovascular surgery at a tertiary referral hospital, who were equally randomized to receive a single dose of either FEIBA or matched placebo intraoperatively at the end of CPB. Results Twenty patients were screened and 12 were randomized and included in the analysis. Protocol adherence was high, and all patients received the study drug per intention-to-treat except one patient. There were no protocol deviations or events of unblinding, and adverse events were not different between groups. Patients in the FEIBA group were older and more likely to be female and had higher BMI, lower hematocrit, and longer hypothermic circulatory arrest. There were no differences in post-randomization blood product transfusions (difference FEIBA vs. placebo −899 mL; 95% CI −5206 to 3409) or in the administration of open-label FEIBA. Conclusions This pilot trial confirmed the adequacy of the trial design that involved the early, blinded administration of FEIBA, by demonstrating excellent protocol adherence. We conclude that a larger trial establishing the effectiveness of early prothrombin complex concentrate administration to reduce the use of blood products in the setting of high-risk cardiac surgery is feasible. Trial registration ClinicalTrials.gov, NCT02577614 . Registered 16 October 2015